ANALISIS PERHITUNGAN BIAYA STANDAR GUNA MENINGKATKAN EFISIENSI BIAYA PRODUKSI (Studi Pada Perusahaan Makanan Ringan “Mawar” Malang) - Mochammad Rudianto (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
In the period of 2012 the company showed a loss occurs the difference in production costs consist of the cost of raw materials ,direct labor costs, factory overhead costs , then you should immediately conduct necessary management improvements standard cost and production cost planning carefully before making the production process so that the company can works efficiently and can reduce production costs in order to remain cost competitive with market prices. Snacks Company